The Convoluted Tubules of the Nephron Must Be Considered Elliptical, and Not Circular, in Stereological Studies of the Kidney - Marta Ortega-Martinez; Vanessa Gutierrez-Davila; Esthefania Gutierrez-Arenas; Alberto Niderhauser-Garcia; Ricardo M. Cerda-Flores; Gilberto Jaramillo-Rangel (Karger Publishers, 2021)
Introduction: The diameter and area of the proximal convoluted tubule (PCT) and the distal convoluted tubule (DCT) are of the main parameters analyzed in stereological studies of the kidney. However, there is no consensus about if the PCT and DCT should be considered circular or elliptical in shape. Objective: To analyze if there are significant differences in the diameter and area of the PCT and DCT, depending on whether they are considered circular or elliptical. Methods: Paraffin-embedded sections of kidneys from CD1 mice were stained with hematoxylin and eosin and examined using a light microscope. Images were captured using a camera linked to image analysis software. A short diameter (d) and a long diameter (D) were measured in both PCT and DCT. A small circular area (SCA), a large circular area (LCA), and an elliptical area (EA) were calculated with mathematical formulas that incorporate d and D values, while a program area (PA) was provided by the software. Results: There was a significant difference between d and D in both PCT (F = 1.354, Sig = 0.000) and DCT (F = 4.989, Sig = 0.000). Also, there were significant differences in the tubular areas in both PCT (F = 34.843, Sig = 0.000) and DCT (F = 22.390, Sig = 0.000); circular areas were different from elliptical areas (SCA and LCA vs. EA and PA). Conclusion: The convoluted tubules of the nephron must not be considered circular, but rather elliptical; care should be taken every time the tubules are analyzed in stereological studies of the kidney, especially when evaluating their diameters and areas.